Creative housing : from provision to enablement : contexting housing policy through the investigation of support structures - Richardson, Robert Richard (School of Architecture, Planning and Geomatics, 2016)
In South Africa, the pressure on the infrastructure and facilities of the city - designed for a privileged few and now accessible to a growing populace - has resulted in two generic conditions. Urban economic centres have either relocated to areas outside of the city- exacerbating sprawl and destroying our urban legacy, or, as in the case of Cape Town, as a result of topography; the racial and political boundaries constructed by the colonial and apartheid state have been replaced by social and economic divisions. The coincidence of the natural topographic assets of Cape Town and the resultant eccentric focus of the city constructed by such topography has created a reversal of the normal population densities of the city. The most densely populated suburbs occur on the periphery while the economic opportunities still exist mainly in the centre. The resultant daily migration to and from work, creates huge pressure on public transportation and infrastructure. The desire for urbanization and the scarcity of affordable resources creates numerable urban pathologies which manifest themselves on the boundary between the periphery and interior. Rapid urbanization and the incapacity of the state to cope in the provision of accessible and affordable housing has resulted in the development of resilient self-aided local typologies which can accommodate the realities of the South African condition• It is my thesis that these local types form a necessary context through which housing design and urban policy should be informed, in order to create an alternative approach to housing in our country.